Homer and the good ruler in antiquity and beyond - Klooster, Jacqueline.; Van den Berg, Baukje. (Mnemosyne, Supplements, 2018)
Homer and the Good Ruler in Antiquity and Beyond focuses on the important question of how and why later authors employ Homeric poetry to reflect on various types and aspects of leadership. In a range of essays discussing generically diverse receptions of the epics of Homer in historically diverse contexts, this question is answered in various ways. Rather than considering Homer's works as literary products, then, this volume discusses the pedagogic dimension of the Iliad and the Odyssey as perceived by later thinkers and writers interested in the parameters of good rule, such as Plato, Philodemus, Polybius, Vergil, and Eustathios.